Does regulation of skeletal muscle function involve circulating microRNAs? - Aoi, Wataru; Sakuma, Kunihiro (Frontiers in Physiology, 2014)
MicroRNAs (miRNAs) are small non-coding RNAs involved in posttranscriptional gene regulation. Recently, growing evidence has shown that miRNAs are taken in by intracellular exosomes, secreted into circulation, and taken up by other cells. Circulating levels of several miRNAs are changed in diseases such as cancer, diabetes, and cardiovascular diseases; therefore, they are suggested to regulate functions of the recipient cells by modulating protein expression. Circulating miRNAs (c-miRNAs) may also modulate skeletal muscle function in physiological and pathological conditions. It has been suggested that acute and chronic exercise transiently or adaptively changes the level of c-miRNAs, thus posttranscriptionally regulating proteins associated with energy metabolism, myogenesis, and angiogenesis. Circulating levels of several miRNAs that are enriched in muscle are altered in muscle disorders and may be involved in their development and progression. In addition, such c-miRNAs may be useful as biomarkers to determine various interactions between tissues and also to reflect athletic performance, physical fatigue, incidence risk, and development of diseases.